Law on civil appeals - Bhagat, Y.P. (New Delhi, 2015)
This book explain the studies on the laws relating to appellate jurisdiction, the subject has already been covered by the earlier comments on CPC. It has exhaustive studies on legal topics is also an important aspect of the legal profession. Hence, subject wise specialized book has become demand of these days.
Keywords: Civil appeals-law